Effectiveness of photodynamic therapy on Candida species isolated from oral samples of children exposed and not exposed to HIV - SILVA,Francine Cristina da (2016)
ABSTRACT Objective: Identify yeast species isolated from unexposed, exposed and HIV-carrier children, and verify the effectiveness of low power laser photodynamic therapy (PDT) on the yeasts species belonging to the Candida genus. Methods: Fifty children assisted by the Public Health Program of the city of Vitória da Conquista, Bahia, were selected and divided into three groups: unexposed to HIV, exposed to HIV during pregnancy, and HIV-carrier. Saliva samples were collected in a disposable sterile universal container and were plated to Sabouraud dextrose agar supplemented with 0.1 mg/mL chloramphenicol. The plates were incubated at 37°C for 48 h. Three strains of each patient were identified by using an API 20 C AUX system. The strains were submitted to photodynamic therapy (PDT) with a 660 nm low power laser and methylene blue dye at different times of irradiation (90, 180 and 282 sec.). Results: The results showed that the most prevalent species was Candida albicans followed by Candida famata (second most prevalent in unexposed to HIV and HIV carriers)) and Candida parapsilosis (second most prevalent in exposed to HIV group). The CFU/mL of Candida spp. decreased significantly (p<0,05) in all groups treated with PDT compared to the controls. Photodynamic therapy treatments at different exposure times (e.g., PS+L90+, PS+L180+, PS+L282+) revealed that the exposure time of 282 sec. gave the highest reduction of the mean logarithmic CFU/mL. Conclusion: Candida albicans was the most prevalent Candida species in these three groups and Candida non-albicans species, when combined, amounted to a significant percentage of Candida isolates. Photodynamic therapy was effective in inactivating the Candida spp. isolated from the oral cavity of children not exposed to HIV, exposed to HIV and HIV-carriers, with the best photodynamic therapy irradiation time being 282 sec.